Investigation of the Effect of Life Kinetic Exercise on Performance in Dart Athletes - Yunus Gür, Ibrahim Halil Hamdemirci, Cengiz Taşkin, Sekuş Taşkin (Pakistan Journal of Medical & Health Sciences, 2022)
The aim of this study is to examine the effect of life kinetic exercises on performance in darts athletes. A total of 40 volunteer women, aged between 12 and 14, residing in Kilis city center and playing darts, participated in the study, 20 of which were in the experimental group and 20 in the control group. Life kinetic exercise was applied to the experimental group for 8 weeks along with dart training. In the control group, only dart training was applied. The data were analyzed in the SPSS package program. Normality analysis of the data was done with the Shapiro-Wilk test. Paired Sample T-Test was used for the comparison of normally distributed data within groups. At the end of the study, statistically significant improvements were detected in the comparison of the pre-test and post-test values ​​of the experimental group. It is identified that there was not any significant difference between the comparison of the pre-test and post-test values ​​of the control group. As a result, it can be said that life exercises applied to dart athletes contribute to the increase of sports performance by providing improvements in the mental and physical skills of individuals.